Janadesh, People's Verdict - Alvarez, Enric; Ampuero, Oriol (Spain; Barcelona: Fundació Quepo, DL 2010, 2010)
Janadesh is the most important non-violent protest movement since Gandhi's times. Over 30 days, 25,000 men and women from the poorest areas of India walked along the 350 km highway that separates the city of Gwalior and the Indian Parliament, in Delhi. Their goal: to start a widespread hunger strike to demand the fair redistribution of land. These warriors without weapons believe that their sacrifice, discipline and personal suffering are better tools than guns to bring about social change.
Verzio Film Festival Submission
Keywords: Documentary films